Factors Affecting Small and Medium Micro Enterprises (Msmes) in Taking Business Capital Financing in Peer to Peer Lending Institutions Sharia Qazwa.Id - Muhammad Sayyid Farras; Rachmat Risky Kurniawan; Muhammad Isman almaududi (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2021)
This study aims to determine what factors influence MSMEs in taking business capital financing at a sharia financing institution, peer to peer lending namely qazwa.id. This study uses a descriptive qualitative method with a non-probability namely sampling technique, purposive sampling. The results of this study indicate that there are three factors that influence MSMEs in taking business capital financing in qazwa, namely easy and fast access to financing, margins and the sharia system. Among these three factors, the factor that greatly influences MSMEs in taking business capital financing at qazwa is the sharia system used by qazwa, namely mudharabah and murabahah contracts as evidenced by the results of interviews the majority of 4 out of 10 respondents chose it.